Experiences and perceptions of Zimbabwean migrant women accessing antenatal and infant/child immunisation in public healthcare services in Gauteng South Africa (2015-2017) - Saburi, Susan (My University, 2017)
Globally, access to maternal and child healthcare remains a fundamental human right for all, regardless of an individual’s migration status (1). People migrate for a variety of reasons, and this mobility brings forth implications for health provision, health care experiences and human rights, both for the migrants and their host population (2, 3). An increasing number of cross-border or international migrant women globally report difficulties in access to and use of healthcare services, including maternal and child health (4, 5). Little evidence in South Africa on these issues proposes that there is a need for deeper knowledge in this regard. South Africa is a signatory to a range of international commitments that place emphasis on the non-discriminatory provision of health services and a progressive health policy assuring health for all, including free access to antenatal care (ANC) (1). Despite this, South Africa’s maternal and child health outcomes continue to be poor - including that of migrants (6, 7). The increased number of migrants from neighbouring countries is perceived to have placed a burden on the South African healthcare system (4). The aim of this study was to explore the experiences and perceptions of Zimbabwean cross-border migrant mothers in accessing routine antenatal care, obstetric care and infant/child immunisation in public healthcare facilities in, Gauteng, South Africa (2015-2016). Through a qualitative study design, the researcher gathered data by means of 13 face-to-face interviews with a purposive and snowball sample of participants. Few participants gave positive reports on the quality of ANC and immunization services they had received. It is therefore important to ensure that this positive care is maintained across all public health facilities in order to instill confidence among health recipients. However, most of the study participants experienced barriers in accessing quality routine ANC and infant immunisation in the country’s public health facilities. These challenges include language barriers, discrimination and poor nurse-patient relationships. Based on these findings and conclusions, the researcher recommends that the South African National Department of Health addresses some of the challenges affecting cross-border migrant vi women in accessing maternal health care in public facilities nationally through the formulation, implementation and follow-up of policies. Furthermore, health care providers need to be continuously educated and motivated to respect the rights of all patients, regardless of an individual’s migration status, in order to instil positive attitudes and quality care. There is also a need to conduct further research in other provinces of the country, preferably with cross-border migrant women from other countries, and draw comparisons with South African women in order to take appropriate steps to address the challenges.
A research project submitted to the School of Public Health in partial fulfilment of the requirement for the Degree of Master of Public Health, in the field of Social and Behaviour Change Communication. Date: June 2017
Keywords: Prenatal Care